Frontline Science: Superior mouse eosinophil depletion in vivo targeting transgenic Siglec‐8 instead of endogenous Siglec‐F: Mechanisms and pitfalls. Issue 1 (5th March 2020) - Knuplez, Eva; Krier‐Burris, Rebecca; Cao, Yun; Marsche, Gunther; O'Sullivan, Jeremy; Bochner, Bruce S.
Abstract: Eosinophils are important multifunctional granulocytes. When studying eosinophil function and its contribution to diseases, mouse models are often used. Mouse eosinophils selectively express sialic acid‐binding immunoglobulin‐like lectin (Siglec)‐F. Its closest functional paralog on human eosinophils is Siglec‐8. These Siglecs are being used to target eosinophils when exploring their mechanistic roles in disease and for potential therapeutic benefit. In order to facilitate preclinical studies of human Siglec‐8, we developed transgenic mouse strains expressing human Siglec‐8 only on the surface of eosinophils with or without endogenous Siglec‐F and have begun characterizing various cellular functions in vitro and in vivo. Eosinophils from Siglec‐8+ mice, with or without Siglec‐F, responded to Siglec‐8 antibody engagement in vitro by up‐regulating surface CD11b, whereas Siglec‐F antibody had no such effect. Engagement of Siglec‐F or Siglec‐8 with respective antibodies in vitro resulted in only modest increases in cell death. Administration of rat Siglec‐F antibodies to mice led to a significant decrease in Siglec‐F surface expression on eosinophils due to internalization, and thus appeared to decrease eosinophil numbers based on Siglec‐F+ cells, but with proper gaiting strategies did not in fact result in significant eosinophil depletion. In marked contrast, administration of mouse Siglec‐8 antibodies rapidly and effectively depleted eosinophils from blood and spleens of mice, but an F(ab′)2 version did not, indicating an Fc‐mediated mechanism for eosinophil depletion in vivo. Siglec‐8 expressing mice with or without endogenous Siglec‐F will be useful to study Siglec‐8‐based therapeutics, and may be a preferred approach when acute or chronic eosinophil depletion is needed. Abstract : Limitations of using certain antibodies that target Siglec‐F in order to deplete mouse eosinophils are best addressed by administering anti‐Siglec‐8 antibody as shown in Siglec‐8 transgenic mice. .